Simulated Evolution and Learning 10th International Conference, SEAL 2014, Dunedin, New Zealand, December 15-18, Proceedings - Dick, Grant; Browne, Will N.; Whigham, Peter; Zhang, Mengjie; Bui, Lam Thu; Ishibuchi, Hisao; Jin, Yaochu; Li, Xiaodong; Shi, Yuhui; Singh, Pramod; Tan, Kay Chen; Tang, Ke (Theoretical Computer Science and General Issues, 2014)
This volume constitutes the proceedings of the 10th International Conference on Simulated Evolution and Learning, SEAL 2012, held in Dunedin, New Zealand, in December 2014. The 42 full papers and 29 short papers presented were carefully reviewed and selected from 109 submissions. The papers are organized in topical sections on evolutionary optimization; evolutionary multi-objective optimization; evolutionary machine learning; theoretical developments; evolutionary feature reduction; evolutionary scheduling and combinatorial optimization; real world applications and evolutionary image analysis.